pl.
.
.
.
.
.
.
.
.
.
.
.
.
s.
.
.
.
.
Anexe:
Răspunsuri la întrebare
Răspuns de
4
Răspuns:
Explicație pas cu pas:
4^(√x +1) = 8 <=>
2^2(√x +1) = 2³ =>
2(√x +1) = 3 <=>
√x +1 = 3/2 =>
√x = 3/2 - 1 = 1/2
√x = 1/2 =>
x = 1/4
5^ˣ² + 1 = 3125 <=>
5^ˣ²⁺¹ = 3125 = 5⁵ =>
x²+1 = 5 => x² = 4 =>
x₁,₂ = ±√4 => x₁,₂ = ±2
x₁ = -2 ; x₂ = 2
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă